2015
DOI: 10.1016/j.optcom.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of single-photon cross-phase modulation using metastable xenon in a high finesse cavity

Abstract: Strong saturated absorption at nanowatt power levels has been demonstrated using metastable xenon in a high-finesse optical cavity. The use of metastable xenon allows a high quality factor of Q=2×10 8 to be achieved at relatively high atomic densities without any contamination or damage to the optical surfaces, which is often a problem when using highdensity rubidium or other alkali atoms. This technique provides a relatively straightforward way to produce nonlinearities at the single-photon level with possibl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…The strong nonlinearity demonstrated in this way is consistent with the ability to generate other forms of optical nonlinearities, such as single-photon cross-phase modulation [12], which would have a number of practical applications [1][2][3]. It was previously shown that comparable cross-phase modulation can be obtained using either a gas of atoms or a single trapped atom [13].…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…The strong nonlinearity demonstrated in this way is consistent with the ability to generate other forms of optical nonlinearities, such as single-photon cross-phase modulation [12], which would have a number of practical applications [1][2][3]. It was previously shown that comparable cross-phase modulation can be obtained using either a gas of atoms or a single trapped atom [13].…”
Section: Introductionsupporting
confidence: 79%
“…The observed saturated absorption at these low power levels suggests that this approach should be able to produce other nonlinear optical effects at ultra-low power levels as well. For example, density-matrix calculations show that we should be able to achieve a single-photon cross-phase shift of approximately 20 mrad using our system [12]. That would be sufficient for a number of proposed applications, including quantum computing [2] and quantum key distribution [3].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This proposal satisfies the conditions necessary to realize optical quantum computation using weak nonlinearities as proposed by Munro, et al [30], non-local interferometry as proposed by Kirby and Franson [31,32], and device-independent quantum key distribution [33]. It also supports some recent experimental efforts [34][35][36].…”
Section: Introductionsupporting
confidence: 81%
“…The field amplitude was approximated by a constant value across an effective cavity mode volume, as described in Ref. [23]. The decay and transition rates were calculated using two-photon absorption measurements performed in our lab, combined with published data for the state lifetimes and branching ratios [19][20][21]…”
Section: Theoretical Modelmentioning
confidence: 99%